Exploring Hadith Tarbawi as the Spirit of Islamic Education - Fathurrohman, Fathurrohman; Suharyat, Yayat (International Journal of Global Sustainable Research, 2023)
This tarbawi hadith arises because of social and scientific developments that must be able to be grounded in accordance with the needs of the faculty and the community in the field of education. This study aims to discuss the tarbawi hadith as a foundation in providing Islamic education. This research uses library research methodology. Sources taken from several books on tarbawi hadith. The results of this study show that the study of tarbawi hadith is understood critically, logically, actually and contextually so that it can reveal the concept of hidden pearls of education to be used as guidelines that can be developed in learning Islamic education in the modern era. Studies like this are indeed very much expected by Muslims today who care about Islamic social problems, especially in education, so that there will be no harassment of the sunnah of the Prophet SAW.